Conserving European biodiversity across realms. Issue 1 (16th July 2018) - Giakoumi, Sylvaine; Hermoso, Virgilio; Carvalho, Silvia B.; Markantonatou, Vasiliki; Dagys, Mindaugas; Iwamura, Takuya; Probst, Wolfgang N.; Smith, Robert J.; Yates, Katherine L.; Almpanidou, Vasiliki; Novak, Tihana; Ben‐Moshe, Noam; et al.
Abstract: Terrestrial, freshwater, and marine ecosystems are connected via multiple biophysical and ecological processes. Identifying and quantifying links among ecosystems is necessary for the uptake of integrated conservation actions across realms. Such actions are particularly important for species using habitats in more than one realm during their daily or life cycle. We reviewed information on the habitats of 2, 408 species of European conservation concern and found that 30% of the species use habitats in multiple realms. Transportation and service corridors, which fragment species habitats, were identified as the most important threat impacting ∼70% of the species. We examined information on 1, 567 European Union (EU) conservation projects funded over the past 25 years, to assess the adequacy of efforts toward the conservation of "multi‐realm" species at a continental scale. We discovered that less than a third of multi‐realm species benefited from projects that included conservation actions across multiple realms. To achieve the EU's conservation target of halting biodiversity loss by 2020 and effectively protect multi‐realm species, integrated conservation efforts across realms should be reinforced by: (1) recognizing the need for integrated management at a policy level, (2) revising conservation funding priorities across realms, and (3) implementing integrated land‐freshwater‐sea conservation planning and management.